Non invasive assessment of the frontal sinus: a review - Munjal, Manish; Puri, Sanjeev; Soni, Anshu; Kailey, Vikramjit; Pooni, Navreen; Munjal, Shubham; Singh, Angad Harshbir (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
The Frontal sinus with its peculiar mucociliary drainage affected by pathology at the frontal recess necessitates an intervention, medical or surgical. Current review elaborates upon the role of basic imaging in pre treatment evaluation.